Centralized E-Book Storage using Cloud (International Journal of Current Engineering and Technology, 2015)
It is client side application which uses cloud. In this project we store e-books on cloud and develop browser based application through which client can access desired e-book. E-books stored on cloud are readable and downloadable. Home page of application will contain categories (such as computer engg, it engg. etc.). Each department is further categorized into subjects. E-books related to that particular subject will be displayed alphabetically. Functionality is provided i.e. uploading e-books by the user. The user who wants to upload e-book can send e-book to admin. Based on relevance that e-book will be uploaded by admin.
Keywords: Ubuntu cloud; LAMP; Books